Formulation of Andrographis tablet from the antisolvent semi-purified Andrographis extract - Nattapulwat, Nattawat; Suriyaamporn, Phuvamin; Opanasopit, Praneet; Wetwitayaklung, Penpun (Science, Engineering and Health Studies, 2025)
Andrographis paniculata extract, administered at 180 mg/day of andrographolide for 5 consecutive days, has been used to treat mild cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This research formulated 30 mg film-coated tablets of andrographolide, derived from a partially purified extract of Andrographis obtained using the antisolvent technique. The powdered extract was combined with microcrystalline cellulose and colloidal silicon dioxide to create core tablets through the wet granulation method. These core tablets were then film-coated. The Andrographis extract powder contained 40.27±1.18% andrographolide. The average weights of the core and film-coated tablets were 381.9 mg and 392.4 mg, respectively, each contained 31.0 of andrographolide. The average friability and hardness of the core tablets were 0.12±0.01% and 8.7±0.2 kg, respectively. The film-coated tablets completely disintegrated within 23 min, and the distribution of the extracted content in the tablet was uniform. The Andrographis tablets used in this study met all USP criteria.